2009
DOI: 10.1161/circimaging.108.815050
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Spectrum MRI Tractography Reveals the Presence of a Complex Network of Residual Myofibers in Infarcted Myocardium

Abstract: Background-Changes in myocardial microstructure are important components of the tissue response to infarction but are difficult to resolve with current imaging techniques. A novel technique, diffusion spectrum MRI tractography (DSI-tractography), was thus used to image myofiber architecture in normal and infarcted myocardium. Unlike diffusion tensor imaging, DSI-tractography resolves multiple myofiber populations per voxel, thus generating accurate 3D tractograms, which we present in the myocardium for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 30 publications
(51 reference statements)
4
122
0
Order By: Relevance
“…Examples include high-resolution DTI in mouse hearts. 17 and diffusion spectrum imaging in infarcted rat hearts 20 The design of a phantom needs to balance mimicking biological structure, reproducibility in manufacture, and amenability to characterization and validation. On the one hand, it could be argued that the phantom should recapitulate the branching syncytium and discrete sheet arrangement found in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include high-resolution DTI in mouse hearts. 17 and diffusion spectrum imaging in infarcted rat hearts 20 The design of a phantom needs to balance mimicking biological structure, reproducibility in manufacture, and amenability to characterization and validation. On the one hand, it could be argued that the phantom should recapitulate the branching syncytium and discrete sheet arrangement found in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…This method allows imaging of the architecture of the organization of myocardial fibers with exceptional resolution (13). Using this technique, Sosnovik et al revealed the presence of meshlike networks of orthogonal myofibers within the infarcted rat myocardium (14).…”
Section: Strengths and Weaknesses Of Mr Versus Ct As An Adjunct To Petmentioning
confidence: 99%
“…137 Recently, myocyte fiber tracking with diffusion tensor CMR has shown fiber remodeling in the epicardial viable rim of infarctions with nodes of orthogonal myofiber intersection or contact, which are potential sources of arrhythmia in this region. 138 In cardiomyopathy, the presence of LGE has also been linked to outcomes. In DCM, midwall LGE predicted sudden cardiac death and ventricular tachycardia and was superior to ejection fraction, 71 findings that have now been replicated.…”
Section: Electrophysiologymentioning
confidence: 99%